Transport Phenomena in Pomegranate Fruit: Mechanisms of Weight Loss and Control Strategies - Lufu, Robert (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhDFoodSc)--Stellenbosch University, 2020.